Psychological Stress felt by Employees at Workplace: A Study on Employee Empowerment by examining the Workplace Ostracism and Employee Resilience - Sneha, Sneha; Kapoor, Mala; Kaur, Komalpreet (Journal of Neonatal Surgery, 2025)
The study examines the effect of workplace ostracism relationship with the employee empowerment was investigated that highlight the impact of psychological Stress and its role on the employee empowerment, employee’s resilience. The study discusses in detail about how the workplace ostracism impact the employee engagement level of the employees. The nature of study is qualitative in nature. The result of the study favors the positive role of employee’s resilience behavior and psychological stress is the negative outcome of the workplace ostracism which affect negatively to the mindset of the employees. Hence Organizations need to focus on introduction of such programs that ensure employees about their belongingness with others and improve their bond with peer groups. This will make them more engaged towards the Organizations goals by managing their personal situations.